CAMPAIGN UNIFORMS & PERSONALIZATION OF PARTY LEADERS AS A STRATEGY TO WIN REGIONAL AND PRESIDENTIAL ELECTIONS - Tyastuti Sri Lestari; Amalia Syauket; Bambang Karsono (Adisam Publisher, 2025)
Indonesia’s political landscape has become significantly more open in recent decades, reflecting a maturing democratic system. Electoral competition among political actors is a logical consequence of democracy, and therefore, requires effective strategies to secure political victories. This descriptive qualitative study seeks to examine two key issues: (1) What political imagery is embedded in the use of campaign uniforms? and (2) What image is constructed through the continuous display of a party leader’s photograph during election campaigns? The study is based on recent and relevant secondary data that align with contemporary electoral phenomena. Findings suggest that in the 2014 and 2019 presidential elections, Joko Widodo (Jokowi) successfully employed a symbolic strategy through the use of campaign uniforms, which functioned as political attire throughout the campaign period. These uniforms carry significant semiotic value, symbolizing unity, multi-ethnicity, multiculturalism, and egalitarianism. Through this imagery, Jokowi cultivated a public persona as a democratic and inclusive leader. This visual strategy was further reinforced by the consistent display of the photograph of the PDIP chairperson, who was portrayed as both a unifying force within the party and a transformative figure in national politics. The presence of the party leader served as a political magnet within campaign communication, emphasizing both ideological and constitutional ties between the candidate and the party. The novelty of this study lies in the argument that political parties, beyond merely constructing a strong brand image, must also maintain voter brand loyalty in order to remain competitive in future elections.